2022
DOI: 10.3390/ijms23158207
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Endogenous Oxytocin Levels and the Effects of Exogenous Oxytocin Administration on Body Weight Changes and Food Intake in Polycystic Ovary Syndrome Model Rats

Abstract: Polycystic ovary syndrome (PCOS) is frequently seen in females of reproductive age and is associated with metabolic disorders that are exacerbated by obesity. Although body weight reduction programs via diet and lifestyle changes are recommended for modifying reproductive and metabolic phenotypes, the drop-out rate is high. Thus, an efficacious, safe, and continuable treatment method is needed. Recent studies have shown that oxytocin (OT) reduces body weight gain and food intake, and promotes lipolysis in some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Previous findings indicated that OT administration significantly reduced the area of adipocytes, the serum triglyceride, aspartate aminotransferase level alanine aminotransferase, and alkaline phosphatase in ovariectomized rats [67]. Moreover, according to the results reported by Yamamoto and colleagues [63], an OT-mediated mechanism was involved in obesity and food intake in the PCOS rats. However, in PCOS the authors found a decrease in serum OT levels and no difference in the hypothalamic mRNA expression of OT and OXTR after the acute systemic administration of OT.…”
Section: Discussionmentioning
confidence: 84%
“…Previous findings indicated that OT administration significantly reduced the area of adipocytes, the serum triglyceride, aspartate aminotransferase level alanine aminotransferase, and alkaline phosphatase in ovariectomized rats [67]. Moreover, according to the results reported by Yamamoto and colleagues [63], an OT-mediated mechanism was involved in obesity and food intake in the PCOS rats. However, in PCOS the authors found a decrease in serum OT levels and no difference in the hypothalamic mRNA expression of OT and OXTR after the acute systemic administration of OT.…”
Section: Discussionmentioning
confidence: 84%
“…In addition to well-established roles in the regulation of labor and lactation in female mammals [65], recent studies have shown that OT also has behavioral, psychological, and physiological functions, including metabolism, appetite, and body weight regulation [13,66,67]. In a previous study, we showed that serum OT levels were decreased in long-term DHT-administered PCOS model rats and that supplementation of OT attenuated food intake and body weight in these animals, indicating that OT might be related to the effects of androgens on appetite and body weight regulation [68]. Interestingly, the effects of estrogens on OT are completely the opposite of those of androgens.…”
Section: Effects Of Androgens On Hypothalamic Functionsmentioning
confidence: 80%
“…In addition, Rett syndrome, characterized by dysfunction in neuronal excitation/ inhibition balance, potentially due to deficits in K + / Cl − cotransporter 2, is associated with deficits in an insulin-like growth factor-1 and OT signaling crosstalk during postnatal development; that can be improved by OT administration [176]. Interestingly, OT may be used for the treatment of women who have polycystic ovary syndrome, primary ovarian insufficiency, and uterine fibroids that often cause infertility [177,178]. In women with severe preeclampsia, an intravenous bolus of 5 IU OT following delivery can increase heart rate, decrease systemic vascular resistance, and reduce blood pressure, and thus improve disease severity [179].…”
Section: Discussionmentioning
confidence: 99%